Criminal Acts Against The Law Of Corruption (Case Study Medan District Court No. 45 / Pid.Sus-TPK/2021 / Fr.Mdn jo Medan High Court case No. 33/Pid.Sus-TPK/2021 / PT.Mdn) - Deby Darmayanti; Ruslan Ruslan; Rilawadi Sahputra (International Asia Of Law and Money Laundering, 2023)
In essence, the land has a very important meaning for human life, because the land is the main foundation of all activities carried out. In accordance with the ownership and use of land in Indonesia, there are lands that are controlled by state-owned institutions, one of which is land controlled by PT.Kereta Api Indonesia (Persero). State-controlled land PT.Kereta Api Indonesia (Persero) which was originally to support the potential development process of PT.Kereta Api Indonesia (Persero) itself, now there are many houses and community business activities throughout Indonesia, one of which is in the city of Medan, North Sumatra province, there are many areas on the edge of the railway where on each edge there are houses and business activities of residents who are renting from the land assets of PT.Kereta Api Indonesia (Persero). The problem raised in this thesis is the lease of land assets of PT.KAI (persero) Division I North Sumatra which led to the conviction in the verdict of committing acts against the law of corruption, because they do not want to fulfill their obligations to pay rent, while the requirements of Article 2 and Article 3 of the UUPTPK are acts against the law (Wederrechtelijkheid) or abuse of control that begins with a violation of procedure or, contrary to the rules or deviations from the authority provided for in the law on procurement of government goods and services, the procedure starts from planning, the need until the completion of all activities to obtain government goods/services with the aim of enriching themselves or benefiting themselves, causing financial losses to the state. While the unlawful acts committed by the defendant include the scope of civil (Onrecht Matiq Overheidsdaad) which is private (vide Article 1365 of the Civil Code) and can file a tort claim in the form of reimbursement of costs, losses, and interest as in Article 1243 of the Civil Code and Article 1267 of the Civil Code.